Alexander the Great and Scipio Africanus - Moore, Kenneth R. (Polskie Towarzystwo Filologiczne, 2019)
This article explores some literary and historical connections between the representation of the Roman general and statesman Publius Cornelius Scipio Africanus and the famous world-conqueror Alexander III of Macedon (the Great) in Polybius of Megalopolis’ fragmentary Book X of the Histories. Recourse is made to Polybius’ source material, as we understand it, as well as other borrowings that he appears to have used in his writings that deal with Alexander. The inquiry delves further into the primary source material available to Polybius and considers some epistemological issues concerning the order in which the Alexander subject-matter was produced,the agendas and circumstances of those who produced it, along with the political and other agendas influencing both its production and its later reception by the time of Polybius. It is clear that Polybius has used the Alexander material as a kind of template for eulogising his Scipio, but he has had to do so carefully, and not un-problematically, due to the sensibilities of his contemporaries and target audience in the Roman Republic.
Keywords: Alexander the Great